The Groningen ‘Accident’: NCG Atelier Regiobouwmeester: design for recovery - Zuidema, Enno; Vredenbregt, Pasha; Herngreen , Anna; Kaasschieter , Quiryn; Arbara, Sophia (Journal of Delta Urbanism, 2025)
Between 1986 and 2013, the Province of Groningen in the Netherlands experienced approximately 1,000 minor earthquakes induced by decades of natural gas extraction. Until the major 2012 Huizinge earthquake, these tremors were neither widely acknowledged as a serious issue nor explicitly linked to extraction activities. Despite growing evidence, Dutch gas companies and governmental bodies delayed taking action, often prioritizing corporate interests over socio-environmental concerns. This essay examines the Groningen earthquakes as a socio-environmental "accident"—not as a random event but the outcome of sustained and systemic negligence which beyond physical damage, has led to long-term distrust, governance failures, and fractured communities. This study features the work of the National Coordinator Groningen (NCG) and it’s Regional Architect’s Atelier (Atelier Regiobouwmeester) to explore the recovery timeline, the role of design in rebuilding efforts, and how specific design measures (toolbox) can contribute to regional reconstruction and resilience. The Groningen case underscores the need for a more just and proactive approach to environmental governance and design in peripheral regions affected by resource extraction.